Thematics : interdisciplinary studies - Louwerse, Max.; Peer, Willie van. (Amsterdam ; Philadelphia : J. Benjamins Pub. Co., 2002)
Themes play a central role in our everyday communication: we have to know what a text is about in order to understand it. Intended meaning cannot be understood without some knowledge of the underlying theme. This book helps to define the concept of 'themes' in texts and how they are structured in language use. Much of the literature on Thematics is scattered over different disciplines (literature, psychology, linguistics, cognitive science), which this detailed collection pulls together in one coherent overview. The result is a new landmark for the study and understanding of themes in their eve.
Thematics; Editorial page; Title page; LCC data; Table of contents; Preface; Introduction; Part 1: Structures and processes; Chapter 1: Psychological and computational research on theme comprehension; Chapter 2: Situation models and themes; Chapter 3: Conditions of updating during reading; Chapter 4: Evaluation devices as a coordinating mechanism for story points; Chapter 5: Responding to style; Chapter 6: The definite article the as a cue to map thematic information; Chapter 7: Thematic management in Korean.
Includes bibliographical references and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Comparative literature -- Themes, motives; Littérature comparée -- Thèmes, motifs; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Comparative literature -- Themes, motives; Diskursanalyse; Rezeption; Literatur; Thema; Thema-Rhema-Gliederung; Kohäsion; Textkohärenz; Sprachverstehen; Texttheorie; Erzählforschung; Thema (taalkunde); Literaire thema's.